The Relationship Between Financial Literacy And Risk Perception On Students’ Interest In Using Shopee Paylater In Surakarta City - Taqbira, Firdatul; Susilo, Agus (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
For university students, financial literacy is not merely associated with an understanding of financial products, but also reflects their capacity to assess financial risks when engaging with digital payment services such as PayLater. The increasing adoption of Buy Now Pay Later (BNPL) platforms among students has raised concerns regarding financial behavior, self-control, and risk management within the digital economy, highlighting the need for empirical investigation in this context. This study employed a quantitative associative approach using purposive sampling. The sample consisted of 100 active undergraduate students in Surakarta who had used Shopee PayLater. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using multiple linear regression with SPSS, supported by validity, reliability, and classical assumption tests. The results indicate that financial literacy has a positive and significant effect on students’ interest in using Shopee PayLater. Risk perception also has a positive and significant effect on students’ interest. Simultaneously, financial literacy and risk perception significantly influence students’ interest in using BNPL services. The findings emphasize the importance of improving financial literacy and risk awareness among students to encourage responsible BNPL usage. Sound financial decision-making among young consumers can support sustainable consumption, minimize excessive debt risks, and contribute to financial system stability in the digital economy. This study simultaneously integrates financial literacy and risk perception to explain students’ interest in BNPL services at the city level, particularly in Surakarta. Unlike prior studies focusing on general consumers, this research provides specific empirical evidence from the student segment in Indonesia.